Wadah SIG BioMECs - 1ST International BioMECs Symposium (1ST IBS) / Mohd Zaini Nawahwi ... [et al.] - Nawahwi, Mohd Zaini; Hasan, Dr Nor’aishah; Zainal Abidin, Dr Nurhamimah; Md Yasin, Dr Ida Muryany; Abd Aziz, Dr Amirul Adli; Ahmad, Dr Nor Monica; Hj. Yaacob, Ilyanie; Hasbullah, Nur Intan (UiTM Cawangan Negeri Sembilan, 2022)
On 16-17th March 2022 (Wednesday-Thursday), the 1st International BioMECs Symposium (1st IBS) was organised by Special Interest Group (SIG), BioMECs. This event collaborated with the Centre of Graduate Studies UiTM Cawangan Negeri Sembilan. The symposium was successfully held online via Google Meet and Webex platform. A total of 250 people from local and abroad participated in the event, which commenced at 9.30am from all Malaysian universities, including international participants from Thailand, Pakistan, India, Indonesia, and the Philippines. The whole event was hosted by Mohd Alif Ikhsan Bin hj Akmal Syukri and Dr Nurhamimah Zainal Abidin as the moderator.